Problems in the adoption of information technology service management models: A systematic literature review - Alvarez, Sandra Tauquino; Linares, Ciro Aguilar (Edelweiss Applied Science and Technology, 2026)
This systematic literature review aims to identify and categorize the recurrent problems organizations face during the adoption of Information Technology Service Management (ITSM) models such as ITIL, COBIT, and ISO/IEC 20000. Following the PRISMA guidelines, a systematic review of 72 studies published between 2020 and 2025 was conducted. The PICO strategy was used to define the search string, and studies were sourced from databases including Scopus, EBSCOhost, ScienceDirect, and IEEE Xplore. The analysis reveals a refined taxonomy of adoption problems across six dimensions: Strategic, Organizational, Technical, Resources, Operational, and Contextual. The most prevalent challenges are a lack of top management commitment (78%), resistance to organizational change (82%), and insufficient specialized skills (71%). Emerging challenges related to Agile-ITSM integration (e.g., DevOps) and adoption in SMEs and startups are also identified. The findings indicate that successful ITSM adoption is hindered more by strategic and organizational factors than by technical ones, requiring a holistic approach to change management. This study provides a structured framework for practitioners to anticipate and mitigate implementation risks. It underscores the need for strong executive sponsorship, cultural change initiatives, and tailored strategies for different organizational contexts to increase the likelihood of successful adoption.